Cyclosporine A Combined with Rituximab Successfully Treated Erythropoietin-Induced Pure Red Blood Cell Aplastic Anemia - Honghui Zeng; Hong He; Xintian Shi; Ying Wang; Xin Wei (Case Reports in Nephrology and Dialysis)
Introduction: Erythropoietin-induced pure red blood cell aplastic anemia (EPO-PRCA) is a rare anemia, which presents a significant treatment challenge, often necessitating the cessation of erythropoiesis-stimulating agents and the adoption of immunosuppressive therapies or renal transplantation. Case Presentation: In the present case, the patient developed severe anemia after 2-year EPO treatment and was diagnosed with EPO-PRCA. The treatment with the full dose of corticosteroids and testosterone for 1 month failed to increase his hemoglobin level significantly. Therefore, the patient received the combination therapy of cyclosporine A (CsA) with rituximab, which effectively cleared the anti-EPO antibody. Then, roxadustat was given to improve renal anemia. As Hb level increased gradually, the patient was recovered from EPO-PRCA. Conclusion: This case reported an EPO-PRCA patient was successfully cured by the combination of CsA with rituximab and provided another choice for the treatment of EPO-PRCA in the future.